Sexual Cognitive Behavioral Therapy's Effectiveness on Sexual Awareness and Psychological Functioning in Married Women - Pourrostam, Mahdieh; Haghighat, Sara (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The purpose of this study was to determine the impact of sexual cognitive behavioral therapy on sexual awareness, psychological functioning, and self-control in married women.Method: The research method was a quasi-experimental pre-test and post-test design with a control group. The study population included all married female students at the Islamic Azad University, Garmsar Branch, in 2023. Based on the population, 30 participants (15 in the experimental group and 15 in the control group) were purposively selected and randomly assigned. Data were collected using the Depression Anxiety Stress Scales (DASS) and the Sexual Awareness Questionnaire by Snell and colleagues (1991), along with Dr. Mehrnaz Aliakbari's sexual cognitive behavioral therapy protocol.Findings: The results indicated that sexual cognitive behavioral therapy significantly and positively affected sexual awareness, psychological functioning, and self-control in married women.Conclusions: Therefore, sexual cognitive behavioral therapy can be used to improve psychological functioning and self-control in women.